Answer:
2x(7x - 3)(7x +3)
Step-by-step explanation:
Find common factors between the 2 numbers:
98x^3 - 18x
2x(49x^2 - 9)
now find what numbers multiplied together is 49, and find what numbers added together equals 0 and the product is 3, 7 times 7 is 49 and 3(-3) = 9 while 3 - 3 = 0 so:
2x(7x - 3)(7x +3)
Answer:
He is a person with a profile on brainly. And I do believe that I have him as one of my friends*
*or not :)
Step-by-step explanation:
Answer:
D. 21.
Step-by-step explanation:
The general form of the equation of a circle is:
(x - a)^2 + (y - b)^2 = r^2 where r is the radius.
Comparing:
(x + 5)^2 + (y + 7)^2 = 21^2
So r^2 = 21^2
making r = √21^2
= 21.
plz make me brainliest